Satisfacción de los usuarios con la atención odontológica. Universidad Nacional de Chimborazo, 2019. - Byron Israel, Núñez Arias (2020)
The objective of this research determined user satisfaction with dental care at the clinics of the National University of Chimborazo. This research is non-experimental with a mixed, descriptive, and cross-sectional approach; the data processed using the survey technique and its instrument was a questionnaire itself that validated using Cronbach's alpha (α=0.801). The study sample made up of 100 patients who attended the clinic for dental care, 100 students from the seventh to tenth semester who do their internships, and 22 teachers who supervise the different clinical procedures. User satisfaction with the service received analyzed and the results of the sum of each score characterized as: (Totally Disagree, Disagree, neither agree nor disagree, Agree, totally agree). From the information obtained, it found that 78% of the users satisfied with the treatment received from the students, 100% of the teachers satisfied with the work they do in the clinic, 81% of the student’s state that they do not have the technical assistance to solve the problems. Most patients who come to the clinic have an acceptable satisfaction with (65.8 %) the overall quality of dental care provided. Furthermore, it indicated that there is no relationship or association between satisfaction levels and the sex of the users attending the dental care (p=0.770). Key words: User satisfaction, dentistry, dental clinic.